ANALISIS PERAN AKTOR DALAM IMPLEMENTASI AKSESIBILITAS KERJA BAGI PENYANDANG DISABILITAS DI DAERAH ISTIMEWA YOGYAKARTA - Maulana, Muhammad Akbar; Syarkawi, Syarkawi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to find out and analyze how accessibility to getting jobs for kickers on stability in the Special Region of Yogyakarta. The problem is focused on the actors implementing the policy, namely the Regional Government, Private Companies and NGOs. To approach this problem the theoretical references of Van Meter and Horn are used. The data is collected through interview techniques and documentation which are then processed using Nvivo 12 plus software and analyzed qualitatively. This study concludes that employment opportunities for persons with disabilities have not been carried out optimally due to the absence of aftercare services, namely the follow-up of assistance to persons with disabilities after participating in training and rehabilitation programs by the Regional Government. Besides, there is no law enforcement in the implementation of pro diffable (inclusion) policies to private companies. And the lack of coordination between each implementing actor in efforts to empower persons with disabilities.Keywords: Implementation, Policy, Actor Implementation, Disability